Pemanfaatan Teknologi Learning Management System (LMS) di Unnes Masa Pandemi Covid-19: Utilization of Learning Management System (LMS) Technology at Unnes during the Covid-19 Pandemic - Pratomo, Inge Widya Pangestika; Wahanisa, Rofi (Fakultas Hukum Universitas Negeri Semarang, 2021)
The rapid change of the times, especially in the field of digital technology, universities become catalysts that have an important role in supporting national research and technology. This is what then becomes a supporter in the national development process by creating an Increasingly superior Nation of Indonesia globally. This technology and information have a wide impact on human life, especially in the field of education to support the teaching and learning process to be more efficient and more effective. This educational technology also contributes to the learning skills of various communication media, as well as making it easier to present more concrete information data, especially in universities. Universities should be able to take advantage of technological advances to improve the management and teaching systems in college, it also aims to improve innovation and the quality of teaching, so universities also need to work with the academic community and industry players to be able to improve and create learning methods that will later improve the quality of graduates from universities. Universities must be able to print competitive and qualified human resources in order to be leaders and thinkers of a nation that can determine the development of their country in the future.